BIOLOGI PERBUNGAAN JAHE MERAH ( ZINGIBER OFFICINALE ROSC. VAR. RUBRA - Erlin Rachman (BERITA BIOLOGI, 1998)
A study on floral biology of red ginger (Zingiber officinale var. rubra) was conducted to approach the floral characters and natural obstacles affecting their sexual reproduction. In vivo observation was directly carried out at Treub Laboratory, The R & D Center for Biology, LIPI, mainly on final development aspects of flower: flowering process, anthesis periodicity and pattern,and pollen fertility. The results showed that commonly there was one of more than 20 spikelets in a spike anthesized perday. Final development stage began to be distinguishable from 6.00 or 7.00 am of anthesis day. Anthesis was always begin after 02.00 pm where the earliest was occurred at 02.04 while the latest was 02.55 pm and consist at least of three stages as is initiation, half and full anthesis.The initiation stage was remarkable by calyx breakage,divided into two types of breakage: -type A (directly break, 58.33%) and -type B (indirectly break, 41.67%).The type B group tend to haa shorter duration of anthesis than type A.Generally this variety of ginger has some negative floral characters base on fertility and fruit or seed setting ability such as very low in anthesis frequency, relatively snort duration of anthesis and inefficient stigma anther locality.In other side, this variety also has positive characters of flower such as enough pollen fertility (32 - 45%), low level in flower abortion and never closing flower even at the of the anthesis process